Diffuse Pulmonary Meningotheliomatosis with Sarcomatous Transformation in a Shiba Dog. (August 2019) - Michishita, M.; Fujiwara-Igarashi, A.; Suzuki, S.; Hatakeyama, H.; Machida, Y.; Yoshimura, H.; Yamamoto, M.; Azakami, D.; Ochiai, K.; Ishiwata, T.; Fujita, M.
Summary: A 2-year-old neutered female Shiba dog exhibited laboured breathing for 1 month. Computed tomography of the thoracic cavity revealed multiple nodules (2–5 mm diameter) in the lungs. Grossly, the lungs were firm and normal in shape. The nodules were grey–white in colour. Microscopically, the nodules were non-encapsulated and exhibited an irregular shape. They were composed of polygonal or spindle cells with indistinct cell borders arranged in sheets. The cells had large, round, hyperchromatic nuclei and abundant pale eosinophilic cytoplasm with no atypia. Intrapulmonary arterial emboli and infiltration into the bronchioles were observed. Immunohistochemically, the cells were positive for vimentin and negative for cytokeratin, glial fibrillary acidic protein and α -smooth muscle actin. Ultrastructurally, the cells displayed cytoplasmic processes, desmosomes and intermediate filaments. These findings led to a diagnosis of diffuse pulmonary meningotheliomatosis with sarcomatous transformation. To the best of our knowledge, this is the first report of diffuse pulmonary meningotheliomatosis in a dog.